2019
DOI: 10.2196/10816
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Technology-Based Supportive Educational Parenting Program on Parental Outcomes (Part 1): Randomized Controlled Trial

Abstract: Background Transitioning into parenthood can be stressful for new parents, especially with the lack of continuity of care from health care professionals during the postpartum period. Short hospital stays limit the availability of support and time parents need to be well equipped with parenting and infant care skills. Poor parental adjustment may, in turn, lead to negative parental outcomes and adversely affect the child’s development. For the family’s future well-being, and to facilitate a smoothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
101
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 77 publications
1
101
0
3
Order By: Relevance
“…The participants in this study perceived non-profit apps to be good means of receiving help and support because of their multi-functionality and convenience. Previous studies have found successful results with app-based interventions [25,62]. However, the shortcomings of current apps and other online approaches were evident, including complicated contents, unclear classified navigation, too much irrelevant information, and information with little scientific background, as reported in other studies [61].…”
Section: Discussionmentioning
confidence: 91%
“…The participants in this study perceived non-profit apps to be good means of receiving help and support because of their multi-functionality and convenience. Previous studies have found successful results with app-based interventions [25,62]. However, the shortcomings of current apps and other online approaches were evident, including complicated contents, unclear classified navigation, too much irrelevant information, and information with little scientific background, as reported in other studies [61].…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, Singapore has been undergoing the Smart Nation initiative since 2014 [38], which encourages health care sectors to shift to telehealth in order to optimize resources and overcome manpower constraints. Previous local studies have also seen successful results with supportive technology-based interventions involving the use of online forums and mobile apps [39,40]. Therefore, technology-based supportive interventions in this context are not considered foreign and may be more ideally suited to the needs of new-generation mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found successful results with app-based interventions [26,63]. However, the shortcomings of current apps and other online approaches were evident, including complicated contents, unclear classi ed navigation, too much irrelevant information, and information with little scienti c background, as reported in other studies [62].…”
Section: Discussionmentioning
confidence: 90%